Correlation Functions of the Pfaffian Schur Process Using Macdonald Difference Operators - Ghosal, P. (Symmetry, Integrability and Geometry: Methods and Applications, 2019)
We study the correlation functions of the Pfaffian Schur process. Borodin and Rains [J. Stat. Phys. 121 (2005), 291-317] introduced the Pfaffian Schur process and derived its correlation functions using a Pfaffian analogue of the Eynard-Mehta theorem. We present here an alternative derivation of the correlation functions using Macdonald difference operators.